Immunohistochemical analysis of B-cell lymphoma -2 in pleomorphic adenoma and mucoepidermoid carcinoma - Saede Atarbashi; Maryam Elahi; Mehdi Khani; Vahid Rakhshan (Wolters Kluwer Medknow Publications, 2014)
Background: Salivary gland tumors form a major area in the field of oral pathology. B-cell lymphoma -2 (Bcl-2) is an anti-apoptotic gene with up-regulation in various neoplasms. The aim of the present case-control study was to comparatively investigate the expression of Bcl-2 protein in pleomorphic adenoma (PA) and mucoepidermoid carcinoma (MEC) and assess its potential diagnostic role in differentiating these tumors. Materials and Methods: A total of 28 cases (18 specimens of PA [control] and 10 blocks of MEC [case]) were selected for analysis by streptavidin-biotin peroxidase method with antibody against Bcl-2. The percentage of positive cells was calculated from a minimum of 1000 neoplastic cells and H-score was identified (% positive cells × intensity of staining). Data were analyzed using two-way ANOVA, t-test, Spearman, Chi-square and Fisher tests (α = 0.05). Results: bcl-2 expression was shown in 13 cases (71%) of PA and 3 cases (30%) of MEC. In addition, four cases of PA showed strong staining. There was a significant difference between the expression intensity of Bcl-2 in the two tumors (P = 0.048) according to ANOVA. No correlation was observed between Bcl-2 expression with the size and location of tumors (P > 0.05). Conclusion: Bcl-2 expression might be used for differentiating these tumors. Bcl-2 protein was overexpressed in PA compared with MEC. Hence, it seems that unlike what was observed in PA, Bcl-2 probably does not participate in the pathogenesis of MEC.